2018
DOI: 10.22159/jcr.2018v5i3.24568
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Benefit of Citicoline for Acute Ischemic Stroke ? Systematic Review of Current Evidences

Abstract: Two main strategies have been suggested for the treatment of ischemic stroke including reperfusion and neuroprotection. Citicoline is one of neuroprotector agent that commonly used in ischemic stroke. A systematic review of citicoline focusing only on ischemic stroke has not yet performed. This systematic review aimed to identify the effectiveness of citicoline in patients with ischemic stroke history. A systematic research was performed using PubMed and Cochrane Library as the database. Keywords were: "citico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Agarwal and Patel [ 493 ] in their systematic review on the role of citicoline in the management of patients with acute ischemic stroke concluded that functional outcomes were significantly improved by citicoline in these patients. However, another meta-analysis based only on studies published in Chinese and English, that is with an important bias, citicoline cannot reduce long-term mortality and dependence rate in the treatment of acute stroke [ 573 ], results similar to those obtained by Pinzon and Sanyasi [ 574 ]. Martí-Carvajal et al [ 575 ] published a controversial Cochrane review about the use of citicoline in the management of acute ischemic stroke.…”
Section: Clinical Experiencementioning
confidence: 83%
See 1 more Smart Citation
“…Agarwal and Patel [ 493 ] in their systematic review on the role of citicoline in the management of patients with acute ischemic stroke concluded that functional outcomes were significantly improved by citicoline in these patients. However, another meta-analysis based only on studies published in Chinese and English, that is with an important bias, citicoline cannot reduce long-term mortality and dependence rate in the treatment of acute stroke [ 573 ], results similar to those obtained by Pinzon and Sanyasi [ 574 ]. Martí-Carvajal et al [ 575 ] published a controversial Cochrane review about the use of citicoline in the management of acute ischemic stroke.…”
Section: Clinical Experiencementioning
confidence: 83%
“…Agarwal y Patel [ 493 ], en su revisión sistemática sobre el papel de la citicolina en el tratamiento de pacientes con accidente cerebrovascular isquémico agudo, concluyeron que los resultados funcionales mejoraron significativamente con la citicolina en estos pacientes. No obstante, en otro metaanálisis basado en estudios publicados en chino e inglés, por lo tanto, con un mayor riesgo de sesgo, estos resultados no se han corroborado [ 573 ], resultados similares a los obtenidos por Pinzón y Sanyasi [ 574 ]. Martí-Carvajal et al [ 575 ] publicaron una controvertida revisión Cochrane sobre el uso de citicolina en el tratamiento del accidente cerebrovascular isquémico agudo.…”
Section: Experiencia Clínicaunclassified
“…In legal terminology, there are several interpretations, namely: grammatical interpretation, systematic interpretation, historical interpretation, comparative interpretation, anticipatory interpretation, and teleological interpretation. Philipus M. Hadjon stated their respective meanings as follows: (1) grammatical interpretation: interpret a legal term or sentence according to everyday language or legal language; (2) systematic: with the system of rules as the starting point, interpret the provisions of a law; (3) historical interpretation traces the intention of forming the law as a interpretative historical in terms of finding answers to a legal issue by tracing legal developments (rules) called rechtshistorische interpretative; (4) comparative interpretation of law: endeavouring to resolve legal issues based on rules of subordinate legal systems; (5) interpretation of anticipation: answer a legal issue based on a rule that is not yet valid; and (6) theological: every interpretation is basically theological.…”
Section: Processing and Analysis Of Legal Materialsmentioning
confidence: 99%
“…For instance, the CAISR (Citicoline in Acute Ischemic Stroke Research) study, a single-center, randomized, placebo-controlled, parallel-group trial, compared citicoline with placebo early after recanalization therapy and two groups showed no significant difference. [ 28 ] Meta-analyses[ 29 , 30 ] did not support the effectiveness of citicoline in acute stroke patients, and a Cochrane review[ 31 ] suggested little to no difference between placebo and citicoline.…”
Section: Introductionmentioning
confidence: 99%